Media advocacy and the actualization of “Vision 2020: the right to sight” in Nigeria: A review - Gambo, Sarah; Shem, Woyopwa; Essien, Coleman Fidelis (Revista Española de Comunicación en Salud, 2024)
Introduction: Nigeria is one of the developing countries that have the highest challenge of Onchocerciasis and other Neglected Tropical Diseases (NTDs) in Africa. Objectives: This study aims at ascertaining the potency, gap and deficiencies of the media in regards to discharging their social responsibility of creating awareness on river blindness and the media’s efforts in the actualization of Vision 2020. Methodology: This research study adopts a documentary research method where the researchers used the Google Scholar to retrieved relevant research journal articles, books, seminar papers and other relevant publications. In order to retrieve relevant materials the following steps were followed identification of keywords, Database Search, Inclusion and Exclusion Criteria, Screening and Selection and lastly Data Extraction and Synthesis. Results: the study found that river blindness (Onchocerciasis) has avalanche of adverse socio-economic effects on the populace of Nigeria. Furthermore, it was also found that media advocacy on Ochocerciasis is dormant and this has the potency to impede the actualization of the World Health Organization’s Vision: 2020 in the country. Conclusion: Communicating information on river blindness using only the conventional media is not enough in a society like Nigeria; hence there is the need for a combination of the conventional and other interpersonal channels of communication like the church/mosque, market, traditional institutions, etc.
Keywords: Onchocerciasis; Media Advocacy; Vision 2020; Nigeria